2014
DOI: 10.1088/2053-1583/1/2/021004
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional hexagonal tin: ab initio geometry, stability, electronic structure and functionalization

Abstract: We study the structural, mechanical and electronic properties of the two-dimensional (2D) allotrope of tin: tinene/stanene using first-principles calculation within density functional theory, implemented in a set of computer codes. Continuing the trend of the group-IV 2D materials graphene, silicene and germanene; tinene is predicted to have a honeycomb lattice with lattice parameter of a0 = 4.62 Å and a buckling of d0 = 0.92 Å. The electronic dispersion shows a Dirac cone with zero gap at the Fermi energy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(60 citation statements)
references
References 31 publications
7
53
0
Order By: Relevance
“…Naturally, the other group-IV elements have been considered as candidates to have a graphenelike hexagonal, honeycomb structure with similar exceptional properties. Indeed, corresponding 2D structures for other group-IV elements have been predicted and studied theoretically, namely, silicene (Si-based), germanene (Gebased), and stanene (or tinene) (Sn-based) [12][13][14][15][16][17][18]. Different from graphene, in the sheet the silicon atoms are buckled, which makes an electronic system with a partial sp 3 hybridization.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, the other group-IV elements have been considered as candidates to have a graphenelike hexagonal, honeycomb structure with similar exceptional properties. Indeed, corresponding 2D structures for other group-IV elements have been predicted and studied theoretically, namely, silicene (Si-based), germanene (Gebased), and stanene (or tinene) (Sn-based) [12][13][14][15][16][17][18]. Different from graphene, in the sheet the silicon atoms are buckled, which makes an electronic system with a partial sp 3 hybridization.…”
Section: Introductionmentioning
confidence: 99%
“…In a form of 2D stannum, stanene is first proposed by Zhang et al and has drawn broad attention. [11][12][13][14][15][16][17] It is believed that stanene is a 2D topological insulator (TI). TIs are a class of novel condensed matter with insulating band gap in the bulk while conducting states at the edges (for 2D TIs) resulted from strong SOC effect and protected by time reversal symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…While all elements in Group IV share electronic features similar to its lightest element, C, the favorable hybridization state for Si, Ge, and Sn is somewhere between sp 2 and sp 3 . This leads to buckled crystal lattice structures rather than planar as observed in graphene, although a planar polymorph of 2D Sn has also been experimentally synthesized on silver substrates . In a recent study, Matusalem et al suggested the MoS 2 ‐like symmetry to be most stable for stanene, while large honeycomb dumb‐bell (LHD) geometry (Figure ) was reported to be more stable for silicene and germanene .…”
Section: Crystal Allotropes Of Elemental 2d Materialsmentioning
confidence: 99%
“…While silicene and germanene also possess nonzero Z 2 invariants and therefore the possibility for the QSHE, their small spin–orbit splitting makes it only possible at low temperature . Stanene, however, has been predicted to possess an appreciable spin–orbit gap of around 70 meV …”
Section: Unique Properties Of Elemental 2d Materialsmentioning
confidence: 99%
See 1 more Smart Citation